Analysis on the safe distance between shield tunnel through sand stratum and underlying karst cave. Issue 2 (4th March 2019) - Wang, Wei; Gao, Shiming; Liu, Lingfeng; Wen, Wushuang; Li, Ping; Chen, Jianping
ABSTRACT: When a subway tunnel passes through a karst geological area, in order to ensure the stability of the tunnel, the safe distance between the tunnel and karst cave needs to be researched. This article is based on the construction project of Wuhan metro line 6 from Qianjincun station to Mayinglu station. In view of the geological condition of overlying sand and underlying limestone, by using numerical simulation and theoretical calculation and selecting a characteristic section, the influence law and degree of karst cave span, height-span ratio, and filling degree on the safe thickness of karst cave roof are studied and a forecasting model of the safe thickness of karst cave roof is established. Combined with dichotomy and numerical simulation, the critical horizontal safe distance beyond which cave collapse does not cause tunnel instability is calculated. The results show that: (1) the safe thickness of karst cave roof increases linearly with the increase of karst cave span, and decreases with the increase of height-span ratio and filling degree; (2) among the three factors, the effect of karst cave span is the most significant, the filling degree of karst cave is the second, and the influence of height-span ratio of karst cave is the weakest; (3) the proposed forecasting model passes the significance test, indicating that the model is very reasonable; and (4) the critical horizontal safe distance from the tunnel border to the karst cave boundary is 22.4 m. The research results can provide guidance for the design and construction of shield tunnels and karst cave treatment in karst areas.